Practice and perceived barriers regarding prevention of Pressure ulcer among nurses of a tertiary care hospital - Majhi, Binita; Pandey Bashyal, Sabita; Ligal, Nani Basi (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: The incidence of pressure ulcers varies between developed and developing countries, with reported rates of 8.3% to 25% in developed countries and 2.1% to 31.3% in developing countries. The estimated cost of treating pressure ulcers is 2.5 times higher than the cost of preventing pressure ulcers. The aim of the study was to assess practices and perceived barriers regarding the prevention of pressure ulcers among nurses at a tertiary care hospital. Methods: An embedded mixed-method design was used to study nurses’ practices and perceived barriers regarding the prevention of pressure ulcers. Through census sampling, 108 nurses from selected wards of Kathmandu Medical College Teaching Hospital were included in the study. Data were collected using a structured questionnaire, observational checklist, and focus group discussion. After data collection, quantitative data were coded and entered into the Statistical Package for the Social Sciences (SPSS) program, version 20. Descriptive and inferential statistics were used. For qualitative data, themes were generated through content analysis. Results: About 65.7% of the participants had good practices for the prevention of pressure ulcers, and there was a significant association between the area of work and training (p ≤ 0.05) with practices. Participants also perceived barriers to prevention practices, such as lack of resources, followed by patient-related barriers like comorbidities. Conclusion: The study findings concluded that nurses’ practices regarding the prevention of pressure ulcers were good, though there were barriers to these practices